(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2010)
Here we describe a Guadalupian brachiopod fauna from units III to V of the shallow water carbonate succession cropping out at Djebel Tebaga de Medenine, South Tunisia. The fauna comprises 29 taxa of the orders Productida, Orthotetida, Orthida, Rhynchonellida, Athyridida, Spiriferida and Terebratulida, whose distribution is consistent with the Wordian-Capitanian age suggested by the associated fusulinids and conodonts. Most of the brachiopod taxa are pedicle attached genera or cemented ones and thus were permanently attached, and only two were free living concavo-convex semi-infaunal genera; this indicates that they were mostly living in high energy environmental settings, where the settling strategies require firm attachment to the substrate at shallow depth under the influence of fair-weather waves. The brachiopods from South Tunisia are very similar to the fauna from the allochthonous limestones of Pietra di Salomone, Rupe del Passo di Burgio and Rocca di San Benedetto of Sosio Valley, Sicily, Italy, a fauna which is also dominated by cemented and pediculate taxa. Both regions were located at palaeoequatorial latitudes in the western termination of the Tethyan Gulf during Middle Permian time.